Childhood Maltreatment and Health Impact: The Examples of Cardiovascular Disease and Type 2 Diabetes Mellitus in Adults. Issue 2 (10th April 2017) - Basu, Archana; McLaughlin, Katie A.; Misra, Supriya; Koenen, Karestan C.
Abstract : Child maltreatment is associated with increased risk of an array of mental and physical health problems. We reviewed studies examining associations of child maltreatment, assessed either alone or in combination with other adversities, with cardiovascular disease (CVD) and type 2 diabetes. A search was conducted in PubMed for relevant studies until December 2015. Forty publications met inclusion criteria. Consistent positive associations were noted across a range of childhood adversities. Child maltreatment was associated with CVD (myocardial infarction, stroke, ischemic heart disease, coronary heart disease) in 91.7% of studies, with diabetes in 88.2% of studies, and with blood pressure/hypertension in 61.5% of studies. Inclusion of mental disorders tended to attenuate associations. Sex‐related differences were under‐examined. Implications for future research and intervention efforts are discussed.